PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GOOGLE CLASSROOM PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR DI SMK NEGERI 3 PANGKEP - Dian Ekawati Nur; Abdul Muis Mapalotteng; Syafiuddin Parenrengi (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
The study aimed to discover 1) The influence of using google classroom learning media on learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep, 2) the influence of learning motivation on learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep,and 3) the influence of using google classroom learning media and learning motivation on learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep. The research method used was ex-post facto research. The total population was 67 people. The sample size was 67 people because this study worked on the population. Data collection was conducted by using documentation and questionnaire. The prerequisite test used the normality test and linearity test. Hypothesis testing employed simple linear regression test and multiple linear regression. The results of the study reveal that: (1) students' perceptions on the use of google classroom learning media in Computer and Basic Network subject at SMKN 3 Pangkep are in